2016
DOI: 10.1021/acs.jpcc.6b01016
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Energetics, and Dynamics of Cs+ and H2O in Hectorite: Molecular Dynamics Simulations with an Unconstrained Substrate Surface

Abstract: International audienceClassical molecular dynamics simulations were performed for the smectite clay hectorite with charge-balancing Cs+ cations using a newly developed structural model with a disordered distribution of Li/Mg substitutions in the octahedral sheet and the fully flexible CLAYFF force field. Calculations for systems with interlayer galleries containing 0–19 H2O/Cs+ suggest that the monolayer hydrate is the only stable state at all relative humidities at ambient pressure and temperature, in agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(145 citation statements)
references
References 113 publications
34
111
0
Order By: Relevance
“…42 Importantly, the Cs + -OCO2 RCN here is very similar to that of Cs + -OH2O in Cs-hectorite in equilibrium with pure H2O. 49 This result is in good agreement with our recent experimental results, which suggest that replacement of H2O by CO2 in the 1L structure of Cs-hectorite under the conditions here requires only a small energy change. 17 The mean non-bonded OCO2 -Ob and OCO2 -OCO2 interatomic distances in Cs-hectorite are centered at 3.4 Å and 3.2 Å, respectively, and the OCO2-Ob RCN is ~7.7 (Figure 4a).…”
Section: Figures 3a 3c 3e) Clearly Show That the Intercalated Co2 Dsupporting
confidence: 89%
See 1 more Smart Citation
“…42 Importantly, the Cs + -OCO2 RCN here is very similar to that of Cs + -OH2O in Cs-hectorite in equilibrium with pure H2O. 49 This result is in good agreement with our recent experimental results, which suggest that replacement of H2O by CO2 in the 1L structure of Cs-hectorite under the conditions here requires only a small energy change. 17 The mean non-bonded OCO2 -Ob and OCO2 -OCO2 interatomic distances in Cs-hectorite are centered at 3.4 Å and 3.2 Å, respectively, and the OCO2-Ob RCN is ~7.7 (Figure 4a).…”
Section: Figures 3a 3c 3e) Clearly Show That the Intercalated Co2 Dsupporting
confidence: 89%
“…Recent experimental and computational modeling studies have clearly shown that the clay swelling behavior depends strongly on the nature of the charge balancing cation (characterized by the CO2 and H2O solvation energies) and on the composition and location of the permanent structural charge of the clay. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Experimental and computational modeling studies have shown that at reservoir conditions the amount of intercalated CO2 and its structural, dynamical, and energetic properties depend on the basal spacing and the solvation energies of the charge-balancing cation with H2O and CO2 in smectite interlayers under supercritical conditions (scCO2, Tc~31ºC, Pc~73 bar). X-ray diffraction (XRD) studies at pressurized CO2 conditions by Giesting et al 18,19 showed that increase (expansion) of the basal spacing of the common smectite, montmorillonite, depends on the initial interlayer H2O content.…”
Section: Introductionmentioning
confidence: 99%
“…37,[39][40][41][42] Because the ions and molecules in the interlayer galleries of smectite clays are structurally and dynamically disordered, their molecular scale behavior is difficult to study with diffraction methods, and in recent years experimental spectroscopic methods and computational molecular modeling have been widely employed. 1,2,5,[7][8][9][10][11][12]43 This paper reports the results of an experimental, variable temperature 23 Na nuclear magnetic resonance (NMR) and computational molecular dynamics (MD) modeling study of the structural and dynamical behavior of Na + in the widely investigated smectite clay, hectorite. The 23 Na NMR behavior of hectorite has been studied previously, 1 but the results here provide more comprehensive understanding, because the spectra were obtained at a higher H 0 eld strength (850 MHz 1 H frequency) and over a wider range of temperatures and water contents.…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed in detail below there is growing evidence that smectite T-O-T layers are exible and dynamic, and thus that their interlayer galleries could be comparably dynamic. 11,12,[33][34][35][36][37][38]…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulation was performed based on identical simulation protocol of Desmond v3.6 package to model the different states of host‐guest ( PBMMA‐ Gd 3+ ) complex for 10 ns time trajectory with 1 ns integration step . Optimized Potentials for Liquid Simulations (OPLS) all‐atom force field 2005 was applied for the cubic periodic box containing Simple Point Charge (SPC) (10 Å × 10 Å × 10 Å).…”
Section: Methodsmentioning
confidence: 99%